MDSCs in breast cancer: an important enabler of tumor progression and an emerging therapeutic target - Liu, Haoyu; Wang, Zhicheng; Zhou, Yuntao; Yang, Yanming (Frontiers in Immunology, 2023)
Women worldwide are more likely to develop breast cancer (BC) than any other type of cancer. The treatment of BC depends on the subtype and stage of the cancer, such as surgery, radiotherapy, chemotherapy, and immunotherapy. Although significant progress has been made in recent years, advanced or metastatic BC presents a poor prognosis, due to drug resistance and recurrences. During embryonic development, myeloid-derived suppressor cells (MDSCs) develop that suppress the immune system. By inhibiting anti-immune effects and promoting non-immune mechanisms such as tumor cell stemness, epithelial-mesenchymal transformation (EMT) and angiogenesis, MDSCs effectively promote tumor growth and metastasis. In various BC models, peripheral tissues, and tumor microenvironments (TME), MDSCs have been found to amplification. Clinical progression or poor prognosis are strongly associated with increased MDSCs. In this review, we describe the activation, recruitment, and differentiation of MDSCs production in BC, the involvement of MDSCs in BC progression, and the clinical characteristics of MDSCs as a potential BC therapy target.